Durables and Lemons: Private Information and the Market for Cars - Richard Blundell; Ran Gu; Søren Leth-Petersen; Hamish Low; Costas Meghir (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2019)
We specify an equilibrium model of car ownership with private information where individuals sell and purchase new and second-hand cars over their life-cycle. Private information induces a transaction cost and distorts the market reducing the value of a car as a savings instrument. We estimate the model using data on car ownership in Denmark, linked to register data. The lemons penalty is estimated to be 18% of the price in the first year of ownership, declining with the length of ownership. It leads to large reductions in the turnover of cars and in the probability of downgrading at job loss.
Keywords: D15; D82; E21; 330; Lemons penalty; car market; estimated life-cycle equilibrium model